Stress Resistance of Biofilm-type Bifidobacterium longum subsp. longum and Its Effect on Intestinal Microbiota - Shuang YAN; Wenming CUI; Yuqin WANG; Wenjie ZHANG; Haoyan ZHANG; Yuzheng CAI; Gaiming ZHAO; Xiaopeng WANG (Shipin gongye ke-ji)
In order to improve the activity of Bifidobacterium in the production and application process, biofilm-type Bifidobacterium longum subsp. longum BOA-7 was prepared with dietary fiber as carrier. The survival rate of biofilm-type BOA-7 under different stress environments and its adhesion ability to HT-29 cells and mucins were analyzed. Furthermore, in vitro fermentation was conducted to examine its effects on intestinal microbiota. The results showed that the survival rates of biofilm cells after hydrogen peroxide treatment, heat treatment at 65 ℃ for 30 min, freeze-drying and simulated gastrointestinal juice treatment were 2.91, 2.10, 1.69 and 5.67 times higher than those of the planktonic group, respectively. The adhesion ability of biofilm-type bacterial cells to HT-29 cells and mucin was more than doubled compared to the planktonic group. The results of in vitro fermentation showed that the addition of biofilm-type BOA-7 significantly (P<0.05) affected the microbial composition of the fermentation system, and increased the relative abundance of Bifidobacterium genus and the absolute number of Bifidobacterium longum. After 24 hours of fermentation, the relative abundance of Bifidobacterium and absolute quantity of Bifidobacterium longum in the biofilm group reached 25.96% and 1.81×109 CFU/mL, respectively, which were 2.01 times and 1.84 times higher than those in the planktonic group. In addition, the analysis of short chain fatty acids showed that the content of acetic acid, propionic acid, and butyric acid in the biofilm group was significantly (P<0.05) higher than that in the control group and the planktonic group. These results indicate that using dietary fiber as a carrier to prepare biofilm-type Bifidobacterium longum subsp. longum can improve the strain's stress resistance, adhesion ability and proliferation rate in the intestine. This study can provide theoretical approaches and data references for the development and application of highly active bifidobacterial microecological agents.